2010
DOI: 10.1111/j.1469-8137.2010.03201.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant sex on range distributions and allocation to reproduction

Abstract: Summary• Despite an abundance of theory, few empirical studies have explored the ecological and evolutionary consequences of sex. We used a comparative phylogenetic approach to examine whether transitions between sexual and asexual reproduction are associated with changes in the size and distribution of species' geographical ranges, and their investment in reproduction.• Here, we reconstructed the phylogeny of the genus Oenothera sections Oenothera and Calylophus (Onagraceae), which contain 35 sexual and 30 fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 72 publications
1
57
0
Order By: Relevance
“…We also show that the self-compatible, relatively smallflowered O. perennis, previously described as autogamous (Straley 1977), actually has a pollination system involving small and medium bees of the family Halictidae and the genus Bombus. This is a surprising result because O. perennis is well known for having a permanent translocation heterozygote (PTH) genetic system (Johnson et al 2009;Johnson et al 2010). Typically, PTH species selfpollinate prior to the flowers opening, and therefore, any visitors are not important or effective pollinators (Johnson et al 2009;Johnson et al 2010;Brown and Levin 2011).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…We also show that the self-compatible, relatively smallflowered O. perennis, previously described as autogamous (Straley 1977), actually has a pollination system involving small and medium bees of the family Halictidae and the genus Bombus. This is a surprising result because O. perennis is well known for having a permanent translocation heterozygote (PTH) genetic system (Johnson et al 2009;Johnson et al 2010). Typically, PTH species selfpollinate prior to the flowers opening, and therefore, any visitors are not important or effective pollinators (Johnson et al 2009;Johnson et al 2010;Brown and Levin 2011).…”
mentioning
confidence: 73%
“…This is a surprising result because O. perennis is well known for having a permanent translocation heterozygote (PTH) genetic system (Johnson et al 2009;Johnson et al 2010). Typically, PTH species selfpollinate prior to the flowers opening, and therefore, any visitors are not important or effective pollinators (Johnson et al 2009;Johnson et al 2010;Brown and Levin 2011). However, for the populations of O. perennis included in this study, we observed that the receptive stigmas, without pollen on their surface, were exserted out of the opening buds of the flowers.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…3, 4). These differences mimic the large distribution ranges and/or poleward expansions in self-fertilizing and asexual plants (Johnson et al 2010). The extended distribution of parthenogenetic lineages toward the poles could stem from enhanced colonization abilities in these lineages, for example because parthenogenesis confers reproductive assurance ["Baker's law"; (reviewed by Pannell et al 2015)] and/or because parthenogens have an advantage over sexual relatives in colder climates.…”
Section: Discussionmentioning
confidence: 99%
“…The idea behind this use of path analysis is to explore the influence that life history traits have on predicting invasiveness, either directly through a causal relationship, and/or indirectly through a correlation with native range size. Such an approach is well suited to reveal novel insights into predicting invasiveness, since previous studies give us the a priori expectation that strong correlations exist between life history and geographic range size (Brown et al 1996;Johnson et al 2010), life history and invasiveness (Pyšek and Richardson 2007), and geographic range size and invasiveness (Goodwin et al 1999;Kolar and Lodge 2001;Pysek et al 2009). Based on this expectation, we predicted that life history traits and native range size would be strong determinants of invasiveness in Silene, but that the effect of individual life history traits would involve both direct and/or indirect correlations, mediated by the enormous variation in geographic range size in this diverse genus.…”
Section: Introductionmentioning
confidence: 98%